Electron diffusion by chorus waves: effects of latitude-dependent wave power spectrum - Yu, Jiang; Wang, Jing; He, Zhaoguo; Chen, Zuzheng; Li, Liuyuan; Cui, Jun; Cao, Jinbin (Frontiers in Astronomy and Space Sciences, 2023)
In the present paper, we investigate the effects of latitude-dependent wave power spectrum on the interactions of chorus with electrons. Great errors in evaluating the electron diffusion coefficients and the resultant electron temporal evolutions are introduced by the widely adopted latitudinally constant model, compared with the latitudinally varying model. The latitudinally constant model tends to overestimate (underestimate) the diffusion coefficients for electrons below (above) 200 keV. The overestimation and underestimation are mainly confined in small to intermediate pitch angles, increase with decreasing pitch angles, and can reach up to several orders of magnitude. The large differences in diffusion coefficients significantly alter the net changes of electron phase space densities and the resultant shapes of electron pitch angle distributions. Our simulations demonstrate that the wave power spectrum distribution along the magnetic field line plays an important role in controlling the dynamics of radiation belt electrons.